Social Norms and Expectations about Student Loans and Family Formation. Issue 1 (26th March 2021) - Kuperberg, Arielle; Mazelis, Joan Maya
Abstract : Social norms and expectations regarding marriage or childbearing while in debt—or with an indebted partner—may explain links between student loans and lower family formation rates. This study analyzes an original survey of college students (N = 2, 990) at two universities examining how student loans will, would, or should affect romantic relationship and family formation decisions. A significant minority believed marriage should be delayed and nearly half believed childbearing should be delayed when people have student loan debt. Many reported they would hesitate to marry someone with high student debt, their loans would delay family formation, and they would form families earlier if their debt were forgiven. Those with loan debt and higher debt were more willing to partner with those who had high student debt. Women were less likely to believe people should delay childbearing and marriage because of loans, but more hesitant to marry a partner with high student debt. Findings suggest social norms underlie childbearing and marriage delays among those with loans, and student loan debt creates a class divide among the highly educated.